(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The main question of this paper is the stress-strain state prediction of the vertical shaft’s combined lining located at the interface of two layers of dolomite and salt. The study predicts geomechanical processes at the contact of the dolomite layer and the salt layer in the vicinity of the vertical shaft’s expanded section, taking into account the operating life of the vertical shaft equal to 50 years. The results combined lining’s stress-strain state, represented as a four – layer medium, where the external layer is concrete, and the three inner layers are used to account for the heterogeneity of cast-iron tubing are compared with the results received when taking into account the pipe structure in explicitly. The solution of the problem was carried out in a three-dimensional statement. The calculation of the tubing lining, considering its actual geometry, will rise the accuracy of the forecast of the stress state of the lining, which in turn will favorably affect the justification of its parameters.